Asynchrony between urban expansion and water environmental protection reshapes the spatial patterns of nitrogen and phosphorus concentrations and N:P stoichiometry in inland small water bodies in Changsha, China - Zhou, Jiaogen; Li, Ying; Lei, Qiuliang; Feng, Qingyu; Luo, Jiafa; Lindsey, Stuart (Frontiers in Environmental Science, 2022)
The asynchrony of urban expansion and urban water environmental protection is a common problem in the process of urbanization. Although urban expansion results in population agglomeration and dramatic changes of land use, it also brings municipal water infrastructures to enhance the water quality of urban water bodies. In order to understand the relationship between water quality and urban expansion and water environmental management, total nitrogen (TN) and total phosphorus (TP) concentrations were measured, which were taken from 68 small urban water bodies in three distance bands (<5 km, 5–10 km and >10 km away from the city center of Changsha City, China) and four main water management types of protection, recovery, degradation and fisheries. The results showed that: 1) with increase in distance away from the city center, TN and TP concentrations in small water bodies and the percentage of polluted samples (IV ∼ inferior V) showed an increasing trend. 2) The degree of protection of small urban water bodies in the study area has not been synchronistic with urban expansion. The protected water bodies (long-term protected and recovering) are mainly distributed in the <5 km distance band, and anthropogenic disturbances (degraded water bodies and small water bodies used for fish farming) were mainly distributed in the 5–10 km and >10 km distance bands. Also, degraded and fish-managed water bodies had higher TN and TP contents than protected and recovering water bodies, but their TN:TP ratios were significantly lower. 3) Overall, urban expansion and water body management contributed 55.8% of the variance of TN and TP concentrations and TN:TP ratios in the study area. Water body management alone contributed 22.2%, which was higher than the contribution of urban expansion (7.6%). This shows that the insufficient application of water environmental protection measures has significantly changed the spatial distribution patterns of N and P concentrations and TN:TP ratios in urban small water bodies as the Changsha urban area has expanded. In the process of urban expansion, the simultaneous development of urban water ecological management is essential to ensure the health protection of the urban water environment.